Evaluation of Hridroga Chikitsa in Chikitsamanjari with special reference to Dhaanyakashuntyadi Ksheerapaka (International Journal of Ayurveda and Pharma Research, 2023)
A well-known Malayalam book that is frequently used by Kerala Ayurveda physicians is Chikitsa Manjari by D. Sreeman Namboothiri. For all types of people, this book offers a wide range of easily understood and acceptable formulations for all aspects of disease. Globally, cardiovascular diseases are the primary cause of mortality. The review of modern pharmacology reveals that the initial cardiovascular medicines were developed from medicinal plants. Clinical practitioners frequently employ these medications. But there is a necessity for documentation of these formulations for the revalidation. Materials and Methods: The literary review of formulations present in Hridroga chikitsa of Chikitsa Manjari was carried out. The different formulations with dosage form and indications are done with special reference to Dhaanyakashuntyadi ksheerapaka in this context. Conclusion: Around 13 formulations are explained in Hridroga chikitsa context. Majority of the preparations are either Ksheerapaka or Kashaya kalpana. The preparations such Ghrita, Taila and Churna are in few numbers. Dhaanyakashuntyadi ksheerapaka has two references in this context with difference in ingredients. The focus of this textbook in Hridroga Chikitsa is on the Snigdha and Ushna prayoga. Hence most of the drugs possess Madhura rasa, Madhura vipaka with Hridya and Balya in action. Having Madhura pradhana rasa- Vipaka and Ushna virya in action, Dhaanyakashuntyadi ksheerapaka have Dipana, Pachana and Vatanulomana. The utilisation of Ayurvedic drugs in the present scenario is very few. This study may pave for the discovery of new cardiac drugs shortly.